(untitled) (CaJoST, 2024)
The study focuses on the comparative assessment on the levels of some physiochemical parameters of well and borehole water collected from five locations in Sokoto metropolis to ascertain their quality index. Samples were collected randomly and analyzed using standard method of analysis. The physiochemical parameters analyzed include; pH, Turbidity, Total Dissolved Solids (TDS), Calcium (Ca2+), Magnesium (Mg2+), Chlorides (Cl- ), Fluorides (F- ) Sulphates (SO4 2+) and Nitrate (NO3 - ). The result of the study was subjected to Descriptive statistics and water quality index. The descriptive statistics results revealed that physicochemical parameters like pH, TDS, SO4 2- , and turbidity are within the WHO limit of drinking water while parameters like Ca2+, Mg2+ and Cl- were within and not within the WHO limit in some sampling locations whereas parameters like F- and NO3 - were found not within the WHO limit in all the sampling locations. The result shows that both water sources were found within excellent and very good water quality index respectively which indicates that both water sources (well and borehole water) consumed within Sokoto metropolis are safe and suitable for drinking as it meets the minimum requirements of WHO standard of drinking water quality.